Echinoid grazing traces on ostreid shell-ground from the Pliocene Ficulle quarry (central Italy) - Riccardo Manni, Letizia Di Bella, Ruggero Matteucci (Journal of Mediterranean Earth Sciences, 2014)
A small shell-ground made of disarticulated valves of ostreids, preserved in a small sandy area in the Pliocene clayey deposit outcropping near the Ficulle Village (central Italy), exhibit a dense and almost exclusive colonization by rasping traces of regular echinoids referable to the ichnospeciesGnathichnus pentax Bromley. Ostreid shells dispersed in the surrounding clayey sediment show deep tier endogenic traces, as Entobia,Gastrochaenolites, Caulostrepsis and Meandropolydora. Only on rare specimens rasping traces coexist with the latter ones. The two bioerosion traces assemblages can be assigned to the two Gnathichnus ad Entobia bioerosion ichnofacies as defined by Bromley and Asgaard ( 1993).